A 1 year Study on Pattern of Neonatal Admissions and Mortality Related to Neonatal and Maternal Influences in A Tertiary Care Teaching Hospital of Barishal (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Morbid conditions during the neonatal period possess a serious risk to the health and well-being of the baby. The death rate among neonates is very high in Bangladesh and various factors are responsible for this other than neonatal diseases.Objectives: The objective was to compare different aspects of neonatal conditions in a tertiary care teaching hospital and to inspect the effects of neonatal/maternal influences over neonatal morbidity and mortality. Another primary goal was to study if there was any interconnection between neonatal morbid conditions and mortality.Methods: This prospective study was carried out at Special Care Neonatal Unit of Sher-e-Bangla Medical College and Hospital, Barishal from April 2019 to March 2020. A total of 142 mothers were enquired according to our questionnaire. Data about both mothers and neonates were included in the questionnaire. Data were analyzed by using SPSS version 26.Results: A total of 142 mothers and their 150 admitted neonates were included in our cohort. Among 150 neonates, we analyzed 133 and excluded 17. During the hospital stay, 9.8% of 133 neonates died. Mortality and morbidity were dependent on factors like gestational age, birth weight, and twin pregnancy. The causes of admission were PNA with HIE (58.6%), neonatal sepsis (28.6%), neonatal jaundice (9.8%), congenital anomalies (8.3%), RDS (4.5%), IUGR (3.8%), pneumonia (2.3%), and diabetes mellitus (0.8%). Neonates having PNA with HIE showed significant p-value when correlated with the cause of LUCS- oligohydramnios, gestational age, birth weight. Pre-term neonates had substantial cases of RDS (9.8%). Neonatal sepsis was observed more on the initiation of breastfeeding on the first day (39.1%) than later (23%), and oligohydramnios, less fetal movement, prolonged labor were found to be significant causes of it.Conclusion: The study acknowledged LBW, PNA with HIE, sepsis, neonatal jaundice, congenital anomalies, and RDS as the major factors for neonatal admissions, and reasons behind mortality were LBW, prematurity, and twin pregnancy. Awareness among parents and improved infrastructure of the hospital might be helpful to reduce the gravity of the condition in the future.DS (Child) H J 2020; 36(1) : 52-60